2001
DOI: 10.1051/forest:2001108
|View full text |Cite
|
Sign up to set email alerts
|

Form function for the `I-214' poplar merchantable stem (Populus � euramericana (Dode) Guinier cv cultivar `I-214')

Abstract: -This paper describes a research and application integrated procedure: the development, evaluation, and use of a form function for the 'I-214' poplar merchantable stem. Because this form function is to be used by timber merchants, a particular emphasis is placed on its sturdiness and reliability. The model is extrapolated to other poplar clones in order to measure the error when using it beyond the range of validity. The limits of the model and possibilities for its improvement are discussed. Its applications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
5
0
1
Order By: Relevance
“…For instance, Roda (2001) reported of poor performance between the relative heights of 0.35 and 0.65 for a 'I-214' popular merchantable stem, and Lee et al (2003) reported of deteriorating performance with increasing height for the modelling of Pinus densiflora in Korea. However in our study, there was virtually no bias along the stem, with the exception of the last 90% of the tree height.…”
Section: Efficiencymentioning
confidence: 97%
See 2 more Smart Citations
“…For instance, Roda (2001) reported of poor performance between the relative heights of 0.35 and 0.65 for a 'I-214' popular merchantable stem, and Lee et al (2003) reported of deteriorating performance with increasing height for the modelling of Pinus densiflora in Korea. However in our study, there was virtually no bias along the stem, with the exception of the last 90% of the tree height.…”
Section: Efficiencymentioning
confidence: 97%
“…In studying the stem taper of a fast growing loblolly pine, Zhang et al (2002) observed that fertilized trees have less taper than unfertilized trees. Young trees were also found to have more tapered stem than ageing or matured trees (Roda, 2001;Ter-Mikaelian et al, 2004). The parameter a, which contributes to the general description of the tapering of the tree, is also a measure of the relative diameter at the base of the stem.…”
Section: The Parametersmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, errors due to volume overestimation were of 3.1%, 1.3% and 0.7%, respectively for girth… Error propagation has also been shown to be significant in the construction of taper equations and in data application to other models (e.g. Roda, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Poplar plantations cover approximately 900,000 hectares throughout Europe (Ball et al, 2005). On poplar plantations, the basal area (g) of trees is estimated based on its girth (Steenackers et al, 1993;DeBell et al, 1998;Meiresonne et al, 1999;Roda, 2001), and such basal area estimations are used during the rotation to predict volume at the final felling (Rodríguez et al, 2010). Since error in the estimated volume derives directly from error in the crosssectional area estimation, poplar plantations provide a good sample for studying how different ways of estimating the cross-sectional area affect volume estimates.…”
Section: Experimental Datamentioning
confidence: 99%